The analysis of the Influence of Environmental Factors, Organizations and Individuals Against Stress Employees Working In The Department of Industry and Trade of West Sumbawa District - Indra Kusumawati (International Journal of Science, Technology & Management, 2021)
Every Institution of Government, the better it Organizations and Institutions urgently need and understand the importance of Human Resources to be developed, in an attempt to achieve a competitive advantage, which is an important asset for the organization in the process of planning strategic. Anatan and Ellitan (2007:16). This study uses a quantitative approach. The type of research conducted included the study of the cause-and-effect (causality). The purpose of the research is to analyze the factors that significantly influence work stress like environmental factors, organizational factors, and individual factors on the employees of Industry and trade of West Sumbawa District . Methods of data collection in this study using Census Method. Furthermore, the data were analyzed using multiple linear regression analysis. The results of the research that environmental factors, organizational factors and individual factors partially and simultaneously have a significant effect on work stress of employees of the Department of Industry and trade of West Sumbawa District , is evident from the results of the t test each independent variable is large dinandingkan from the t table, and the value of F calculated is greater than F table. Individual factors, is the dominant variable affecting the job stress of employees in the Department of trade and Industry of West Sumbawa District , is known based on the results of the t value which is the largest when compared with the results of other variables.